2004
DOI: 10.1021/la049201x
|View full text |Cite
|
Sign up to set email alerts
|

Sensing Capabilities of Colloidal Gold Modified with a Self-Assembled Monolayer of a Glucose-Carrying Polymer Chain on a Glass Substrate

Abstract: A disulfide-carrying polymer with pendent glucose residues (poly(2-methacryloyloxyethyl D-glucopyranoside)) was obtained by using a benzyl N,N-diethyldithiocarbamoyl derivative which shows the abilities of initiation, chain transfer, and termination (iniferter). The disulfide-carrying polymer was accumulated on a colloidal Au-immobilized glass substrate, and the usefulness of the polymer as a sensing element of concanavalin A (Con A) was examined by using a UV-visible spectrophotometer with the help of surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 68 publications
1
49
0
Order By: Relevance
“…[72] The detection of protease, lectin, glycoprotein, etc., was also examined with the help of LSPR. [73][74][75][76][77] In this section, the LSPR technique was adopted to follow the adsorption of proteins to the surface of polymer brushes (PCMB and PMMA) on the gold colloid. Figure 3 clearly indicates that BSA, HSA, lysozyme, and cytochrome c did not adsorb to the surface of the PCMB brush significantly, whereas substantially adsorbed to the surface of both bare gold colloid and PMMA brush.…”
Section: Adsorption Of Proteins To the Polymer-brush-on-gold Colloid mentioning
confidence: 99%
“…[72] The detection of protease, lectin, glycoprotein, etc., was also examined with the help of LSPR. [73][74][75][76][77] In this section, the LSPR technique was adopted to follow the adsorption of proteins to the surface of polymer brushes (PCMB and PMMA) on the gold colloid. Figure 3 clearly indicates that BSA, HSA, lysozyme, and cytochrome c did not adsorb to the surface of the PCMB brush significantly, whereas substantially adsorbed to the surface of both bare gold colloid and PMMA brush.…”
Section: Adsorption Of Proteins To the Polymer-brush-on-gold Colloid mentioning
confidence: 99%
“…Because each gold colloid particle can be bound with many amino groups, the strong affinity between the gold nanoparticles and the glass surface encourages the immobiliza- tion stable. The DDT/glycolipid modified sensor chip may be more stable at higher salt concentration due to the steric stabilization effect of the bilayers stretching outward from the surface of the colloids (Morokoshi et al, 2004).…”
Section: Stability Of the Sensor Chipsmentioning
confidence: 99%
“…Subsequently, Nath and Chilkoti (2002) showed that an immobilized colloidal Au monolayer could be used to investigate biotin-streptavidin interaction. Moreover, Kitano's group (Morokoshi et al, 2004) prepared gold biosensors modified with a self-assembled monolayer of a glucose-carrying polymer chain for detection of Con A. They further demonstrated that a new label-free optical sensor was able to display biomolecular interaction in real time at the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Hammond and co-workers [18,19] have shown an alternative to these methods that creates a combination of chemical and topographical patterns by printing polyelectrolyte multilayers which then direct the positioning of particles. Patterns obtained using any of these methods can potentially be used for photonic-bandgap devices, [20][21][22] ionic and biological sensors on surfaces, [23] molecular recognition, [24,25] single-electron transistors, [26] and high-density data-storage systems.[27]Nanoparticles have been attached to substrates using immersion in a suspension [15,18] or by procedures based on capillary forces exerted on the nanoparticles. [4,16] -2003-500120) for which financial support is gratefully acknowledged.…”
mentioning
confidence: 99%